Cecal Volvulus as a Rare Complication of Osimertinib Dosed at 160 mg in Patients With EGFR-Mutant Non-small Cell Lung Cancer - Patil, Tejas; Pacheco, Jose M.; Dimou, Anastasios; Purcell, William T.; Rossi, Candice; Bunn, Paul A.; Doebele, Robert C.; Camidge, D. Ross; Ferrigno, Lisa (Frontiers in Oncology, 2020)
Background: Osimertinib is a 3rd-generation tyrosine kinase inhibitor (TKI) that blocks the epidermal growth factor receptor (EGFR) in non-small lung cancer (NSCLC) and has dramatically improved outcomes for patients with EGFR mutations. While gastrointestinal complications such as diarrhea have been reported with EGFR inhibitors (due to off-target interactions with EGFR receptors within the gut lining), cecal volvulus is an extremely rare complication in advanced malignancy. To date, there are no reported cases associating cecal volvulus with any EGFR TKIs. Case Presentation: In this case series, we present three cases of cecal volvulus among patients with EGFR-positive NSCLC patients treated with osimertinib dosed at double the standard 80 mg dose (160 mg daily). No patient was receiving concurrent chemotherapy or bevacizumab at the time of this described complication. In two cases where pathology was available for review, peritoneal carcinomatosis or intra-abdominal spread was not observed. In a retrospective evaluation of 101 patients treated with osimertinib in our institution, there was a statistically significant difference in the incidence of cecal volvulus among patients receiving osimertinib at 160 mg vs. patients receiving the 80 mg dose (27 vs. 0%; p < 0.001). Conclusions: To our knowledge, these are the first cases to highlight a potentially important and serious gastrointestinal complication associated with the 160 mg dose of osimertinib.